Mount Milligan alkalic porphyry Au--Cu deposit, British Columbia, Canada, and its AEM and AIP signatures: Implications for mineral exploration in covered terrains - Kwan, Karl; Müller, Daniel (Journal of applied geophysics, 2020)
Although alkalic porphyry Au--Cu deposits are much less common than their calc-alkalic counterparts, they represent attractive exploration targets both due to their occurrence as, locally concealed, clusters and their high Au contents. In this paper, the geology of the Mt. Milligan Au--Cu deposit, Canada, and its geophysical footprint on magnetic and AEM data is used as a case-study for the exploration and discovery of concealed alkalic porphyry Au--Cu deposits. The Cole-Cole parameters in the AEM data are extracted using an improved Airborne Induced Polarization (AIP) mapping algorithm. We propose that the subtle electromagnetic signatures of disseminated sulfides around the intrusive porphyry stocks at Mt. Milligan could be mapped by the mτ product, where m is AIP apparent chargeability, and τ the Cole-Cole time-constant, provided that the depths of the alteration zone does not exceed 75 m. The product is called Tau-Scaled Chargeability or TSC. In order to improve the exploration success in the search for concealed alkalic porphyry Au--Cu deposits, we propose to: (1) concentrate the exploration on known and well-endowed mineral districts; and (2) apply innovative digital data-processing techniques capable of extracting weak and subtle signatures from airborne geophysical data and, subsequently, to utilize DCIP ground surveys in the follow-up of anomalies, ideally in combination with enzyme-leach soil sampling. •Alkalic porphyry Au-Cu deposits are attractive exploration targets due to their high Au contents.•They occur in clusters, typically above fractionating magma chambers in the upper crust.•AIP mapping can define pyrite halos around concealed intrusive stocks at Mt. Milligan.•AIP mapping can be used as a vectoring tool.